A NEW APPROACH TOWARDS THE MEASUREMENT OF INNOVATION AND TECHNOLOGICAL ACTIVITIES - M. Korres, George; Polychronopoulos, George (Journal of European Economy, 2017)
Innovation activities contribute essentially to competitiveness and growth. Technological infrastructure and innovation capabilities affect not only the regional growth, but also the whole periphery and economy, as well. This paper attempts to analyze the background of innovation statistics and in particular to examine the measurement and also the statistical estimation of innovation activities. The question addressed in this paper, is whether the recent slow-down in productivity can be explained by the slow-down of innovation activities. It attempts to model and measure technical change, in order to measure the corresponding effects of economic growth. Then, the characteristics of innovation process are broadly examined: nature, sources along with the main affecting factors. The paper concludes by summarizing the major findings of the discussion and pointing to some directions for future research. On this context, it also aims to emphasize and to review the appropriate techniques, the most common methods and the particular problems.